The correlation between the gender, age, education level and the anxiety, stress and spirituality levels during the new normal time of the covid-19 pandemic - Widyanita, Feni; Rosyad, Yafi Sabila; Iskamto, Bambang (Sahabat Publikasi Kuu, 2022)
Background: the COVID-19 pandemic has been troubling the community and the uncertainty about the end of COVID-19 led to impacts in terms of health and impacts on gender, age, level of education, anxiety, stress and spirituality. Many factors became stressors during the new normal COVID-19 pandemic, namely gender, age, level of education. The level of anxiety and stress were also related to the level of one's spirituality. The impact of anxiety and stress could lower the immune system. Objective: To determine the correlation between gender, age, education level and the anxiety level, stress and spirituality during the new normal of COVID-19 pandemic. Methods: The research was conducted in Gunungkidul Regency from August-September 2021. This type of research was quantitative using an analytical survey with Cross Sectional approach. The sample in this study was 374 people who were taken by purposive sampling with bivariate analysis of Kendall's tau data, the questionnaires used were DSES and DASS 21. Results: There was no correlation between gender and the anxiety with p value = (0.915) > (0.05), there was no correlation between gender and stress with p value = (0.430) > (0.05), there was no correlation between gender and spirituality with p value = (0.020) > (0.05), there was no correlation between age and anxiety with p value = (0.077) > (0.05), there was no correlation between age and stress with p value = (0.209) > (0.05), there was no correlation between age and spirituality with p value = (0.015) > (0.05), there was no correlation between education level and anxiety with p value = (0.289) > (0.05), there was no correlation between education level and stress with p = (0.024) > (0.05), there was no correlation between education level and spirituality with p = (0.008) > (0.05) during the new normal period of the COVID-19 pandemic. Conclusion: There was no correlation between gender and anxiety, stress and spirituality, there was no correlation between age and anxiety, stress, and spirituality, there was no correlation between education level and anxiety, stress and spirituality during the new normal COVID-19 pandemic.